Synthesis of PVA/PVP based hydrogel for biomedical applications: a review - Husain, Mohamed Saad Bala; Gupta, Arun; Alashwal, Basma Yahya; Sharma, Swati (Taylor & Francis, 2018)
The composition and synthesis of hydrogel were developed by using Polyvinyl alcohol (PVA) and Polyvinylpyrrolidone (PVP). Polyvinyl alcohol (PVA) and Polyvinylpyrrolidone (PVP) based hydrogels are the most popular water-soluble, biodegradable, biocompatible, non-carcinogenic, and extremely low cytotoxicity synthetic polymers due to their good biocompatibility have been used in numerous biomedical applications, such as implants, artificial organs, drug delivery devices, and wound dressings. In this review paper, details of synthetic of hydrogel formulations with PVA and PVP for biomedical applications.